Ultrasonic-Assisted Synthesis of Two t-Butoxycarbonylamino Cephalosporin Intermediates on SiO2 - Feng Xue; Yibin Wei; Shengui Ju; Weihong Xing (Journal of Chemistry)
Herein, we describe a facile and high efficient strategy for the synthesis of two forms of the 7β-t-butoxycarbonylamino-3-chloromethyl-3-cephem-4-carboxylates using ultrasonic irradiation. By SiO2 as weak Lewis acid catalyst, 4-methoxybenzyl 7β-t-butoxycarbonylamino-3-chloromethyl-3-cephem-carboxylate (Boc-ACLE) and benzhydryl 7β-t-butoxycarbonylamino-3-chloromethyl-3-cephem-4-carboxylate (Boc-ACLH) were successfully synthesized through the efficient protection of the N-t-butoxycarbonyl (N-Boc), and the reactions occurred at low temperature requiring short reaction times and exhibiting excellent isolated yields (96% and 96.2%, resp.). The advantages of this reaction route including the usage of economical reagents and mild reaction conditions and high isolated yield make the two significant t-butoxycarbonylamino cephalosporin intermediates possible in large-scale production.